Pakistan Clean Fuels - World Bank (Washington, DC, 2014)
In the context of the Pakistan Clean Fuels Program, and subsequent workshops, the study reviews the proposed timetable for phasing lead out of gasoline, increasing the average of gasoline octane, and reducing sulfur in diesel, and fuel oil. Within South Asia, Pakistan remains one of the countries using leaded gasoline widely, and, given the extensive epidemiological evidence concerning the adverse impact of lead on public health, lead elimination is the highest priority for fuel quality improvement, in addition to the pollutant concern of high ambient concentrations of fine particles. Also examined is the aspect of particulate emissions: higher contribution by diesel vehicles to particulate emissions, a factor aggravated by the much lower pricing policy of diesel. Workshops findings suggest that incremental costs of reducing sulfur in diesel is low, compared to the cost of reducing sulfur in fuel oil which is substantial, arguing for an accelerated switch from fuel oil to natural gas. Conversely, the incremental cost of eliminating lead in gasoline, and reducing sulfur in diesel is surprisingly low. If implemented successfully, one effective option is differentiated vehicle taxation, by which diesel vehicles are taxed considerably more than gasoline equivalents, so as to make diesel vehicles economically unattractive. However, findings suggest that fuel tax policy alone is a poor instrument for inducing a shift from diesel to gasoline powered vehicles; observations thus highlight the importance of coordinating policies across environmental, transport, and energy sectors, using a number of policy instruments, rather than just one to address these problems.